(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Diabetes mellitus is a growing global health concern nowadays in which women are more prone because of metabolic and hormonal risk factors. Insulin resistance act as a central link between prediabetes , polycystic ovary syndrome which eventually leads to type 2 diabetes mellitus . Even prediabetes in young women remains undiagnosed and left untreated. PCOS is a endocrine hormone disorder which is strongle associated with insulin sentivity. This paper explores the interconnection between prediabetes , PCOS and type 2 diabtes mellitus in women and emphasizing how insluin contributes to metabolic and hormonal disturbance in women. This studies also focus on classification of diabetes in women , role of lifestyle modification for prevention.